A 360-degree view of actor engagement in service co-creation. (January 2018) - Finsterwalder, Jörg
Abstract: In recent years, discussion surrounding the construct of customer engagement in service research has gained significant attention from academics and practitioners alike. The discussion of engagement, an important topic for service research, has focused on the customer, neglecting the roles of other actors, such as employees, who can play a large part in the value co-creation process. This paper is a call-to-action for academics to include a 360-degree view of engagement into the service research discourse. The employment of a service ecosystems perspective is suggested to include engagement from an actor-to-actor perspective. The objective is to focus on all actors who intend to participate, already actively participate in, or actors who are disengaged from the value co-creation process in such systems.